Effect of different alcohol levels on take-over performance in conditionally automated driving. (June 2018) - Wiedemann, Katharina; Naujoks, Frederik; Wörle, Johanna; Kenntner-Mabiala, Ramona; Kaussner, Yvonne; Neukum, Alexandra
Highlights: Comparisons of placebo, 0.05% and 0.08% BAC in a high-fidelitydriving simulator. Drivers were distracted from the driving environment by a simple NDRT. 0.08% BAC significantly worsened take-over time and vehicle control. 0.05% BAC did only go along with descriptive impairments in fewer parameters. Future research should further address more complex NDRTs. Abstract: Automated driving systems are getting pushed into the consumer market, with varying degrees of automation. Most often the driver's task will consist of being available as a fall-back level when the automation reaches its limits. These so-called take-over situations have attracted a great body of research, focusing on various human factors aspects (e.g., sleepiness) that could undermine the safety of control transitions between automated and manual driving. However, a major source of accidents in manual driving, alcohol consumption, has been a non-issue so far, although a false understanding of the driver's responsibility (i.e., being available as a fallback level) might promote driving under its influence. In this experiment, N = 36 drivers were exposed to different levels of blood alcohol concentrations (BACs: placebo vs. 0.05% vs. 0.08%) in a high fidelity driving simulator, and the effect on take-over time and quality was assessed. The results point out that a 0.08% BAC increases the time needed to re-engage in the driving task and impairs several aspects of longitudinal and lateral vehicle control, whereas 0.05% BAC did only go along with descriptive impairments in fewer parameters.